1999
DOI: 10.1136/ard.58.4.214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcome of septic arthritis in a single UK Health District 1982-1991

Abstract: Conclusions-Septic arthritis continues to be associated with a considerable degree of morbidity and mortality. These results confirm the importance of obtaining synovial fluid and blood for culture before starting antimicrobial treatment. The apparent poorer outcome found with surgical intervention is in line with some previous suggestions but should be interpreted with caution in light of the retrospective nature of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
288
7
20

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(344 citation statements)
references
References 14 publications
29
288
7
20
Order By: Relevance
“…Untreated joint infection can lead to irreversible destruction of articular cartilage, disability, systemic sepsis and death [3,4,7]. A retrospective study of septic arthritis in the United Kingdom reported 23.8% of patients had considerable loss of function in the affected joint and 11.5% of patients died as a result of their illness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated joint infection can lead to irreversible destruction of articular cartilage, disability, systemic sepsis and death [3,4,7]. A retrospective study of septic arthritis in the United Kingdom reported 23.8% of patients had considerable loss of function in the affected joint and 11.5% of patients died as a result of their illness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Infection sites that were associated with the highest rate ratio were the joints (rate ratio for SA 14.89 [95% CI 6.12-73.71]), bone (rate ratio for osteomyelitis 10.63 [95% CI 3.39-126.81]), and skin and soft tissues (rate ratio 3.28 [95% CI 2.67-4.07]) [4]. SA is a serious and severe condition for patients that can lead to irreversible joint destruction, and the incidence of SA in the general population is around 4-10/100,000/person-years [5,6]. SA is lethal around 10% of a death rate [7].…”
Section: Risk Of Septic Arthritis (Sa) In Ra Patientsmentioning
confidence: 99%
“…However, conclusive and specific evidence has not been established for the etiology of this disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…Septic arthritis is one of the problems of rheumatological and orthopedic emergency medicine (1,2). The disease is caused by various microorganisms, particularly bacteria, causing destruction of the joint space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation